Accessibility of essential anticancer medicines for children in the Sichuan Province of China - Chen, Zhe; Li, Siyu; Zou, Kun; Li, Hailong; Zeng, Linan; Lu, Xiaoxi; Jia, Zhi-Jun; Cheng, Guo; Zhang, Lingli (Frontiers in Public Health, 2022)
Background: Compared with high-income countries, the survival rate of childhood cancer is lower in low- and middle-income countries. Access to essential anticancer medicines is an indispensable component of pediatric cancer treatment, which is still a big challenge in low- and middle-income countries. Objective: To assess the accessibility of essential anticancer medicines for children in public hospitals in Sichuan Province of China. Methods: Based on the data of the Sichuan Province Drug Use Monitoring Platform in 2020, a retrospective study was conducted to investigate the original brands and generics of 34 anticancer and 3 supportive essential medicines for children (a total of 97 specific strengths) in Sichuan Province. The availability, price, and affordability of surveyed medicines were evaluated in all 152 tertiary public hospitals (120 general hospitals, 31 children's hospitals, and 1 cancer hospital) that could diagnose and treat cancer in children. Results: The average availability of generics and original brands were 18.5% and 2.6%, respectively. In regions with different GDP per capita levels, the average availability was similar, but the city with lower GDP per capita levels had fewer tertiary public hospitals. The prices of most original brands were higher than the lowest-priced generics, and the median price ratios of 31 lowest-priced generics and 16 original brands were 0.694 (P25-P75, 0.368-2.561) and 1.921 (1.668-3.381). After medical insurance paying for medicines, the affordability of essential anticancer medicines was improved. And 78.9% (30/38) lowest-priced generics and 50.0% (8/16) original brands were considered affordable, the monthly medicine cost did not exceed 10% of the monthly household income. Conclusion: The availability of LPGs was higher than OBs in public hospitals, but the availability of both was low. Most poorly available medicines were commonly used, inexpensive and affordable medicines. Although the National Basic Medical Insurance greatly improved the affordability of children’s essential anticancer medicines, higher subsidies for essential medicines for cancer treatment to limit catastrophic health expenditures are still recommended.